2011
DOI: 10.1080/01446193.2011.562911
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the applicability of learning curve theory to formwork labour productivity

Abstract: The learning phenomenon has proved applicable in various industries, especially those associated with mass productions, such as aircraft and automobile assembly. The learning process in labour-intensive industries is assumed to be more significant in the sense that automated work is constrained by the fact that machines cannot benefit from previous experience and therefore would not 'learn' to run any faster or increase the rate of production. Several previous investigations into the applicability of learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 12 publications
0
38
1
5
Order By: Relevance
“…The main production unit of the industry is a temporary organization (such as the SPie project) based on sub-contracting labor provision formed to construct a unique structure ( Jarkas & Horner 2011). The lack of operational permanence is why radical whole-industry change is advocated, and why attempts at implementation have been an ineffective method of increasing industry productivity (Hughes & Thorpe 2014;Kenley 2003).…”
Section: Lessons Learned: Be Incremental Not Aspirationalmentioning
confidence: 99%
See 1 more Smart Citation
“…The main production unit of the industry is a temporary organization (such as the SPie project) based on sub-contracting labor provision formed to construct a unique structure ( Jarkas & Horner 2011). The lack of operational permanence is why radical whole-industry change is advocated, and why attempts at implementation have been an ineffective method of increasing industry productivity (Hughes & Thorpe 2014;Kenley 2003).…”
Section: Lessons Learned: Be Incremental Not Aspirationalmentioning
confidence: 99%
“…In the specific case of a research project, this means actively searching for problems that will not be solvable and eliminating them from the scope of the project (Hughes & Thorpe 2014;Jarkas & Horner 2011).…”
Section: Open Standards Adoption Based On Integrating Practical Limitmentioning
confidence: 99%
“…Subsequently, applications of this concept has spread through other sectors of manufacturing until reaching different areas in the construction industry (Hamade, Jaber, & Sikström, 2009;Hinze & Olbina, 2009;Lam et al, 2001;Wong, On Cheung, & Hardcastle, 2007;Zhang, Zou, & Kan, 2014). Other research works also considered the impact of the learning effect on different site activities such as prestressed concrete and piles (Hinze & Olbina, 2009), rebars Jarkas, 2010), formwork ( Jarkas & Horner, 2011), and caisson construction (Panas & Pantouvakis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these works focussed only on the formwork selection and cost, particularly conventional formworks (Tam et al, 2005;Hanna et al, 1992;Kamarthi et al, 1992;Elbeltagi et al, 2011;Ratary, 1980). A study focussed on exploring the influence of recurring building floor configurations on formwork labor productivity (Jarkas and Horner, 2011). The findings indicated that there was no potential context for the learning curve theory to be used as a useful tool to quantify productivity improvement of formwork installation.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of ACS are as follows (Kamarthi et al, 1992;Hanna, 1999;Elbeltagi et al, 2011;Jarkas and Horner, 2011;Tam et al, 2005):…”
Section: Introductionmentioning
confidence: 99%